PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS IV SDS YKPP SUNGAI PAKNING - Roslina, Roslina; Kurniaman, Otang; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the lack of narrative essay writing skills of students with an average value of data beginning at 65.07. Formulation of the problem in this study is whether the model of cooperative learning can enhance the narrative writing skills of fourth grade students SDS YKPP Pakning ? The research objective is to improve the skills of writing a narrative essay fourth grade students SDS YKPP Pakning with the implementation of cooperative learning model. This design is a class action (PTK) which performed a total of two cycles, each cycle consist of two meetings and one test.. From this research obtained narrative essay writing skills of students of the first test in the first cycle by an average of 72.77, or an increase of 11.83%,at the second test on the second cycle average of 84.11 or an increase of 29, 30%. Results of teacher activity data from the first cycle, meeting 1 of 62.5% is quite at a meeting category 2 by 70.8% good category or an increase of 8.3%, Cycle II meeting 1 of 87.5% is very good category and meetings 2 amounted to 91.6% very good category or an increase of 4.1%. Student activity at the meeting amounted to 58.3% of category 1 sufficient, 2 meeting both categories was 66.6% or an increase of 8.3%. At the first meeting of the second cycle of 79.1% good category and second meetings of 87.5% is very good category or mnegalami an increase of 8.4%. From the results of this research can be concluded that with the Application Model Cooperative Learning Can Improve Writing Skills Narrative Grade IV SDS YKPP Sungai Pakning Kabupaten Bengkalis.Keywords: Cooperative Learning Model, Narrative Writing